Selective Attachment of Gold Nanoparticles to Ionic Liquids Adsorbed Multiwalled Carbon Nanotubes (Journal of Fiber Bioengineering and Informatics, 2018)
Room temperature ionic liquids were adsorbed on the surface of the multiwalled carbon nanotubes (MWCNTs) by electrostatic interaction between carboxyl groups on the chemically oxidized MWCNTs surface and room temperature ionic liquids. The cations of ionic liquids and carboxyl groups on the carbon nanotube surface are put into a one-to-one correspondence by the electrostatic interaction. Negatively charged 15 nm gold nanoparticles are subsequently anchored to the surface of the MWCNTs through the electrostatic interaction between the ionic liquids and the gold nanoparticles. Gold nanoparticles are selectively attached to chemically functionalized surface sites of carbon nanotubes. This approach provides an efficient method to attach other nanostructures to carbon nanotubes and can be used as an illustrative detection of the functional groups on carbon nanotube surfaces.
Keywords: Carbon nanotubes; surface treatment; gold nanoparticles; modification; ionic liquids